The Influence of Digital Marketing Strategies on Generation Z Consumer Behavior in Azerbaijan - Talibov, Ali (2025)
This study explores the impact of digital marketing strategies on Generation Z's purchasing behavior in Azerbaijan, focusing on visibility, influencer effects, personalization, and promotional campaigns. The study reveals important demographic factors on online purchasing preferences using a systematic survey and quantitative analysis; age turns out as a major influencer. Younger respondents (18–22 years) demonstrate more online buying preferences than their older colleagues; work situation and education level have no appreciable effect. The results highlight as main drivers of buying behavior the need of exposure through brand commercials, influencer-driven marketing, and confidence in strong digital presence. Promotional strategies—especially discounts and incentives—are successful in attracting this budget-conscious group. To properly engage and convert this technologically engaged generation, companies aiming at Generation Z must implement thorough strategies combining exposure, peer-driven influence, trust-building, and creative yet pragmatic marketing techniques, the survey finds.